AB0247 Rheumatoid arthritis patient characteristics at different therapeutic timepoints. (23rd January 2014) - Ng, N.; Humby, F.; Kelly, S.; Di Cicco, M.; Dadoun, S.; Bombardieri, M.; Hands, R.; Rocher, V.; Pyne, D.; Kidd, B.; Pitzalis, C.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease whose pathogenesis and response to therapy may differ at different therapeutic time points. While an immune-mediated inflammation may drive early disease, at late stages, a stromal reaction may prevail. Consequently tailored therapy within any phase of the disease requires better appreciation of both clinical, imaging and histopathological phenotypes. Objectives: This study aims to investigate if there are any significant differences in these features at three distinct RA therapeutic timepoints. Methods: Data was collected from 54 RA patients from 3 time points i)early RA (EAC), n=20, onset <1 year & prior to starting disease modifying anti rheumatic drug (DMARD) ii) DMARD inadequate responders (DMARDir), n=20, failed ≥2 DMARDS & fulfilling national criteria to start anti TNF and iii) anti TNF inadequate responders (TNFir), n=14, failed ≥1 anti TNF & switching to different biologic agent Prior to changing therapy, all patients had a core data set assessment including clinical, biochemical and imaging including ultrasound (US) of metacarpophlangeal joints and writsts, scored using Eular score (0-3). Patients also underwent an US guided synovial biopsy of a symptomatic joint. Sections of paraffin embedded RA synovial tissue were stained with standard Haematoxylin and Eosin and graded as either a diffuse or aggregate synovitis. Sequentially cut paraffin sections also underwent immunohistochemical staining for B-cells(CD20), T cells (CD3) and macrophages (CD68) and were semi-quantitatively scored (0-4) for each marker. Results: Study population was 75% female with a mean age of 53. Mean disease duration was 0.5 years (EAC), 6.9 years (DMARDir) and 15.2 years (TNFir). DAS28 were similar between groups (p = 0.38). Rheumatoid factor and anti-CCP positivity were more prevalent in the DMARDir and TNFir cohorts (p<0.001). US imaging showed no significant difference in the amount of grey scale synovitis (p = 0.78) between groups but significant differences were seen in the amount of Doppler signal between groups (p=0.036). Histological grading was significantly different between groups (p<0.04), with 64% of TNFir group having a diffuse synovitis. Lower levels of T cells (p<0.04) and B cells (p<0.02) within the synovium were also noted in this group. Interestingly, we found a significant correlation between US synovitis with the presence of sublining macrophages in the EAC and DMARDir groups (p<0.01 and p=0.04) which is lost in the TNFir group. Conclusions: The association between US synovitis and sublining macrophages, which have been suggested to be predictive of treatment response do suggest that US findings need to be always considered in the context of therapeutic agent and disease duration. Furher studies is needed to evaluate the utility of US to predict treatment response as well. The predominance of a diffuse histological pattern in the TNFir group suggests that this pattern may be associated with treatment resistant RA. Further studies will be needed to evaluate its value as a predictor of TNFir. Disclosure of Interest: None Declared